Multiple Approaches to Translating the Poems and Songs in The Essential Tagore - Islam , Mohammad Shafiqul (EAST WEST JOURNAL OF HUMANITIES, 2017)
Rabindranath Tagore (1861-1941), a universal poet winning the Nobel Prize in literature in 1913, draws global attention through translation – his work is retranslated or reformed through new translation from time to time. Whenever Tagore’s work in translation comes into discussion, Gitanjali, a seminal anthology of poems and songs, appears before us since the poet himself translated the book into English. If Gitanjali had not been translated, Tagore, needless to say, would not have drawn attention of the west. As a result, there would be little prospect for him to win the Nobel Prize. Critics take special interest in Tagore’s own translation alongside other translations because his work is still translated and retranslated with a variety of approaches. Many renowned Tagore translators have rendered his work into modern English, eschewing traditional approaches. One of the finest poets from India with his footsteps across borders and cultures, Tagore generates enormous interest among scholars for his vast and varied oeuvre translated in multifarious ways. Taking Radha Chakravarty’s observation that “translating Tagore today can be interventionist, transformative, and even utopian” into account, this paper attempts to explore multiple approaches that the translators have undertaken to render a selection of his poems and songs into English published in The Essential Tagore (2011).